Market volatility and spillover across 24 sectors in Vietnam - Hung Quang Bui; Thao Phuong Tran; Toan Tan Pham; Hung Le-Phuc Nguyen; Duc Hong Vo (Cogent Economics & Finance, 2022)
While market volatility and volatility connectedness across different financial markets have been examined, the spillover effects across sectors have been under-examined. As such, this study aims to examine market volatility and the volatility patterns for 24 Vietnamese sectors. Our study uses the ARMA-GARCH estimation technique over the 2012-2021 period. The spillover effects between these sectors are then investigated using the vector autoregression (VAR) technique. Three key findings are as follows. First, the market volatility of Development Investment, Education, and Securities is most affected by the market volatility from the previous periods, whereas Construction is least affected. Second, the Vietnamese stock market exhibits a substantial inter-sector connectedness above 60 per cent from 2012 to 2021. However, the sectoral spillover effects increase to around 90 per cent during the Covid-19 pandemic. We found that Aquaculture, Building Materials, Food, and Plastic are the four primary risk transmitters at the sectoral level. Third, market volatility for Energy, Plastic, and Steel is unaffected by the pandemic. Meanwhile, Securities, Fertilizer, and Transportation exhibited a significant increase in market volatility during Covid-19. Based on these empirical results, policy implications have emerged for the Vietnamese government to support affected industries to recover and develop.
Keywords: 330